2018
DOI: 10.1101/421305
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A non-canonical JAGGED1 signal to JAK2 mediates osteoblast commitment in cranial neural crest cells

Abstract: During craniofacial development, cranial neural crest (CNC) cells migrate into the developing face and form bone through intramembranous ossification. Loss of JAGGED1 (JAG1) signaling in the CNC cells is associated with maxillary hypoplasia or maxillary bone deficiency (MBD) in mice and recapitulates the MBD seen in humans with Alagille syndrome. JAGGED1, a membrane-bound NOTCH ligand, is required for normal craniofacial development, and Jagged1 mutations in humans are known to cause Alagille Syndrome, which i… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…The copyright holder for this preprint this version posted June 24, 2020. ; https://doi.org/10.1101/2020.06.24.169755 doi: bioRxiv preprint We previously showed that JAG1 non-canonically signals through NOTCH via phosphorylation of JAK2 during CNC cell osteoblast commitment (8). In this manuscript, we demonstrated increased STAT5 phosphorylation, demonstrating that STAT5 (Fig.…”
Section: Discussionmentioning
confidence: 53%
See 4 more Smart Citations
“…The copyright holder for this preprint this version posted June 24, 2020. ; https://doi.org/10.1101/2020.06.24.169755 doi: bioRxiv preprint We previously showed that JAG1 non-canonically signals through NOTCH via phosphorylation of JAK2 during CNC cell osteoblast commitment (8). In this manuscript, we demonstrated increased STAT5 phosphorylation, demonstrating that STAT5 (Fig.…”
Section: Discussionmentioning
confidence: 53%
“…Our prior research demonstrated that JAG1 signaling is required for CNC cell osteoblast commitment and that conditional ablation of Jag1 in the CNC cells of mice was associated with craniofacial bone loss, recapitulating the facial phenotype seen in Alagille Syndrome patients who have JAG1 mutations (4). JAG1 signaling occurs through cell-to-cell interactions between the JAG1 ligand and NOTCH receptors 1-4 (16)(17)(18) and we previously reported that JAG1-dependent CNC cell osteoblast commitment occurs primarily through non-canonical JAG1-JAK2 signaling (8).…”
Section: Introductionmentioning
confidence: 84%
See 3 more Smart Citations